Pengaruh corporate social responsibility, ukuran perusahaan, struktur modal dan profitabilitas terhadap earning response coefficient - Silva Dara, Liza; Kadir, Kadir; Nailiah, Rusma (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to (1) examine and analyze the effect of corporate social responsibility (CSR) on earnings response coefficient (ERC); (2) examine and analyze the effect of firm size on ERC; (3) examine and analyze the effect of capital structure on ERC; (4) testing and analyzing the effect of profitability on ERC. The sample data in this study were selected using the nonprobability sampling method with the sampling technique in the form of purposive sampling so that there were 22 manufacturing companies listed on the Indonesia Stock Exchange that met the criteria. Data were analyzed using multiple linear regression on SPSS. The results of this study indicate that corporate social responsibility has no effect on earning response coefficient. Firm size and profitability show a positive influence on the earning response coefficient. Meanwhile, the capital structure shows a negative effect on the earning response coefficient.